Demenz Naturwissenschaftliche, rechtliche und ethische Aspekte - Knell, Sebastian (Ethik in den Biowissenschaften, 2022)
This expert report informs about the medical basis of dementia's cluster of symptoms, outlines pertinent legal norms, and discusses connected ethical problems. Dementia comprises a cluster of symptoms primarily characterized by an impairment of cognitive abilities. It brings about significant changes in a wide range of areas for the persons who are affected as well as for their social environment. Interacting with persons affected by dementia therefore involves normative challenges. This also raises questions regarding legal capacity, medical care, and pertinent instruments for adult guardianship law.